Predictor of muscle dysmorphia among members of fitness centers in Denpasar City, Bali, Indonesia - Vennesa Vitari Maureen Susanto; Dewa Nyoman Wirawan; I Putu Adiartha Griadhi (Universitas Udayana, 2020)
Background and purpose: Muscle dysmorphia is one of the most common forms of body dysmorphic disorder. It is part of the obsessive-compulsive disorders, wherein sufferers believe that the body is too small or not muscular enough. The purpose of this study was to determine the predictors of muscle dysmorphia among fitness center members. Methods: A cross-sectional study was conducted at five fitness centers with 117 respondents. Several scales were applied including: 1) 4th edition Sociocultural Attitudes Towards Appearance Scale (SATAQ) to measure self-internalization, family, peer, and media pressures; 2) Physical Appearance Comparison Scale (PACS) to measure social comparison; 3) Body Esteem Scale for Adolescents and Adults (BESAA) to measure respondents’ satisfaction with their bodies and 4) The Muscle Dysmorphic Disorder Inventory (MDDI) to measure muscle dysmorphia. Meanwhile, weight was measured with Kris EB9-4A Series digital scales, height with GEA microtoise and body fat percentage with a digital HBF-306 body fat monitor. Spearman’s Correlation test was performed for the bivariate analysis and multiple linear regression for the multivariate analysis. Results: The prevalence of muscle dysmorphia among fitness center members was 43.6% (95%CI=33.99:53.20) in the total sample based on MDDI cut-off score. Bivariate analysis shows that six variables including body fat percentage, total physical activity, thin/low body fat internalizations, muscular/athletic internalizations, peer pressure, media pressure associated with muscle dysmorphia. In the multivariate analysis, only four variables were significantly associated with muscle dysmorphia, namely: muscular/athletic internalization (β=0.369, 95%CI=0.296:0776, p<0.001), media pressure (β=0.277, 95%CI=0.167:0.595, p<0.001), body fat percentage (β=-0.262, 95%CI=-0.301:-0.067, p=0.002) and body dissatisfaction (β=-0.224, 95%CI=-0.245:- 0.050, p=0.003). Conclusion: The prevalence of muscle dysmorphia in Denpasar City is relatively high. Muscular/athletic internalization, media exposure, body fat percentage and body satisfaction are associated with increase chance of having muscle dysmorphia.